Strategi Komunikasi Pemerintah Daerah dalam Mengatasi Penyebaran Hoaks dan Hate Speech pada Pemilihan Umum di Mandailing Natal - Farid, Ahmad Salman (Journal of Islamic Communication Studies, 2023)
This study aims to evaluate the effectiveness of the communication strategy of the local government in overcoming the spread of hoaxes and hate speech during the general election in Mandailing Natal, Sumatra. The spread of hoaxes and hateful information on social media has become a serious problem that can affect the integrity and stability of the democratic process. The research method is a qualitative approach using in-depth interview techniques and analysis of social media content. The research respondents consisted of government officials, members of the public, and social media users who were active during the general election period. The study results show that local governments have implemented various communication strategies to overcome the spread of hoaxes and hate speech. The strategy includes educational campaigns, building community involvement, and collaboration with the media so that the local government's communication strategy has a positive impact on reducing the spread of hoaxes and hate speech.